2023
DOI: 10.1126/sciadv.ade3876
|View full text |Cite
|
Sign up to set email alerts
|

Cohesin regulates alternative splicing

Abstract: Cohesin, a trimeric complex that establishes sister chromatid cohesion, has additional roles in chromatin organization and transcription. We report that among those roles is the regulation of alternative splicing through direct interactions and in situ colocalization with splicing factors. Degradation of cohesin results in marked changes in splicing, independent of its effects on transcription. Introduction of a single cohesin point mutation in embryonic stem cells alters splicing patterns, demonstrating causa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…Furthermore, recent studies have identified genetic variants of the other meiotic-specific cohesins SMC1β, REC8, and RAD21L associated with infertility phenotypes including POI and NOA [ 76 , 79 , 80 , 81 , 82 ]. Moreover, the recent discovery of cohesin involvement in RNA splicing can provide a potential avenue for investigating the etiology of idiopathic infertility, in which non-null hypomorphic mutations in meiotic cohesins may be disrupting the transcriptional program of gametogenesis [ 83 ].…”
Section: Infertilitymentioning
confidence: 99%
“…Furthermore, recent studies have identified genetic variants of the other meiotic-specific cohesins SMC1β, REC8, and RAD21L associated with infertility phenotypes including POI and NOA [ 76 , 79 , 80 , 81 , 82 ]. Moreover, the recent discovery of cohesin involvement in RNA splicing can provide a potential avenue for investigating the etiology of idiopathic infertility, in which non-null hypomorphic mutations in meiotic cohesins may be disrupting the transcriptional program of gametogenesis [ 83 ].…”
Section: Infertilitymentioning
confidence: 99%